Hyperspectral underwater light field measured during the cruise SO290 with RV SONNE - Daniela Voß; Rohan Henkel; Thomas Henry Badewien; Oliver Zielinski (PANGAEA, 2024)
Data presented here were collected during the cruise SO290 with RV SONNE from Nuoméa (New Caledonia) to Nuoméa (New Caledonia) (April 15, 2022 - Mai, 12, 2022). In total, 19 underwater light profiles were collected at 7 stations, using a free-falling hyperspectral light profiler. The system used was a SEABIRD HyperPro II (SN 099, former Satlantic), equipped with a irradiance sensor to measure downward irradiance in water (Ed, SN 262) and a radiance sensor for the upward radiance in water (Lu, SN 227). A reference unit was attached to the ship to measure the downward irradiance in air (Es, SN 223). The sensors were pre-calibrated by the manufacturer and validated prior to the cruise with a reference lamp. Data were recorded with the SatView software (V 2.9.5_7) and processed from raw to Level1, 1b, 2, 2s to Level 3a using the ProSoft Processing software (V 7.7.19_2). Measured data were binned in 0.5 m depth intervals. A dark correction was made automatically based on shutter measurements by the instrument. Measurements with a tilt higher than 5 were not taken into account during processing. Spectra were interpolated to 1 nm intervals. For each station the hyperspectral profiles for each parameter cover the wavelength range from 400-700 nm, for Ed and Es in [W/m nm], for Lu in [W/m nm sr]. For Ed, Lu and Es descriptive statistics are given including min, max, mean, median and standard deviation of the tilt and the photosynthetically active radiation PAR [μmol photons/m^2 s (sr)], integrated from 400 - 700 nm. To allow an assignment of above water conditions to the respective depth measurements, Es spectra were given as a function of depth, recalculated from data Level2s. The Profiler measurements were only conducted during daylight. Raw data are available on request from the principal investigator.